2018
DOI: 10.1002/mabi.201800041
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Heparin‐Loaded Core–Shell Nanofiber Sutures for Achilles Tendon Regeneration In Vivo

Abstract: Achilles tendon reconstruction surgery is the primary clinical method for repairing acute Achilles tendon ruptures. However, the efficacy of the postoperative healing process and the recovery of physiological function are inadequate. This study examines the healing mechanism of ruptured rat Achilles tendons seamed with heparin-loaded core-shell fiber sutures fabricated via near-field electrospinning. High-heparin-concentration sutures (PPH3.0) perform better than the low-heparin-concentration sutures and comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…A desirable scaffold that possesses both suitable mechanical properties and biological signals is required for tendon tissue engineering [80]. In recent years, novel spinning approaches were used to fabricate scaffolds mimicking the hierarchical structures of natural tendon tissue [81,82], and to accelerate the healing of tendon defects and further induce tendon regeneration. In addition to varying the preparation method, tendon scaffolds containing various bioactive molecules were also fabricated [83,84].…”
Section: Electrospun Scaffolds For Tendon Tissue Engineeringmentioning
confidence: 99%
“…A desirable scaffold that possesses both suitable mechanical properties and biological signals is required for tendon tissue engineering [80]. In recent years, novel spinning approaches were used to fabricate scaffolds mimicking the hierarchical structures of natural tendon tissue [81,82], and to accelerate the healing of tendon defects and further induce tendon regeneration. In addition to varying the preparation method, tendon scaffolds containing various bioactive molecules were also fabricated [83,84].…”
Section: Electrospun Scaffolds For Tendon Tissue Engineeringmentioning
confidence: 99%
“…Recently, to address this issue, several studies have been performed in innovative directions for employing electrospun NYs with great ECM fibril-mimicking characteristics as surgical sutures. From the perspective of suture composition, several absorbent synthesized polymers, such as PLGA [141] , PLLA [142] , PPDO [143] , and PCL [144] , were preliminarily investigated to electrospin them into NYs for surgical suture applications. It was found that the single electrospun NYs exhibited relatively low mechanical properties, which could not satisfy the requirements of practical applications [141] .…”
Section: Tissue Repair and Regeneration Applicationsmentioning
confidence: 99%
“…The results showed that the electrospun nanofibrous suture exhibited negligible immunogenicity, and significantly higher neovascularization was found in the nanofibrous suture than in the commercial microfibrous suture control. Several other studies reported the fabrication of electrospun nanofiber-coverspun yarns to enhance the mechanical properties of as-generated sutures [ 142 , 144 , 145 ].…”
Section: Tissue Repair and Regeneration Applicationsmentioning
confidence: 99%
See 2 more Smart Citations